Blockchain and cryptocurrencies - Stephen Chan; Jeffrey Chu; Yuanyuan Zhang; Saralees Nadarajah (Journal of Risk and Financial Management, 2020)
Cryptocurrencies are essentially digital currencies that use blockchain technology and cryptography to facilitate secure and anonymous transactions. Many institutions and countries are starting to understand and implement the idea of cryptocurrencies in their business models. With this recent surge in interest, we believe that now is the time to start studying these areas as a key piece of financial technology. The aim of this Special Issue is to provide a collection of papers from leading experts in the area of blockchain and cryptocurrencies. The topics covered in this Special Issue includes the economics, financial analysis and risk management with cryptocurrencies.
Keywords: 330; Bitcoin; Blockchain; Cryptocurrencies; Digital Currencies; Financial analysis; Risk management